The use of digital transformation technologies and their impact on the quality of the audit process (A Field Study on Joint-Stock Companies in Benghazi) (Comprehensive Journal of Science, 2025)
This study aimed to examine the extent to which digital transformation technologies contribute to improving the quality of the audit process in joint-stock companies in the city of Benghazi. Specifically, it sought to assess the impact of utilizing digital transformation technologies on the accuracy, efficiency, and professional performance of audit processes. Additionally, the study investigated the extent to which these technologies reduce the time and effort required, and enhance auditors’ ability to perform high-quality audits, particularly in complex cases. The significance of this study lies in the pivotal role digital transformation technologies play in enhancing the performance of the auditing profession. To achieve the research objective, one main hypothesis and two sub-hypotheses were formulated. The target population included financial managers, internal auditors, and external auditors. A questionnaire was employed as the primary tool for data collection, and appropriate statistical methods were used to analyze the data. The findings revealed a consensus among participants on the positive impact of using digital transformation technologies in the auditing field. These technologies contribute to improving and advancing professional performance, reducing errors, and minimizing the time and effort expended. Moreover, they enhance auditors’ ability to efficiently carry out complex audit tasks, expedite report preparation, and reduce reliance on manual work, thereby improving the overall quality and efficiency of audit processes.Based on these findings, the study recommended the need to strengthen the adoption of digital transformation technologies in audit departments within joint-stock companies. This includes developing the necessary digital infrastructure, providing appropriate training for auditors, and integrating these technologies into formal audit procedures. The study also called for updating internal policies to align with the requirements of digital transformation, activating the role of regulatory bodies in supporting this transition, and conducting further field studies to gain a broader understanding of its challenges and opportunities.
Keywords: Digital transformation, Quality of the audit process, Joint-stock companies.